Prof. Hristo Dimitrov and his contribution in the efforts of the Bulgarian Orthodox Church for religious education among children in the period 1944-1948 (Forum Theologicum Sardicense, 2025)
The article presents the Bulgarian Orthodox Church’s efforts to oppose the atheist government, which removed religious education from Bulgarian schools in 1944. Prof. Hristo Dimitrov offers various options to ensure religious instruction for children and youth in this period of Bulgaria’s history. The article chronologically presents the different options for religious education in schools and outside of them, which prof. Dimitrov proposes - more active involvement of the Bulgarian Orthodox Church in the religious education of children and the inclusion of priests in the educational process.
Keywords: Religious Education; Orthodox Church; Atheist Regime